Kepastian Hukum Pembukaan Rekam Medis Pasien COVID-19 Dalam Situasi Pandemi - Apta Daniswara Hardiani Kusuma; Igam Arya Wada (Faculty of Law, University of Jember, Indonesia, 2022)
A medical record is a document made by a hospital containing the identity, examination, treatment, and medical actions taken against confidential patients. Medical records are medical secrets that can be shown or disclosed in certain situations, one of which is a pandemic situation. In the event of an outbreak of infectious disease, namely the COVID-19 pandemic situation, medical records belonging to COVID-19 patients can be used by doctors, hospitals, and researchers to identify and analyze the causes as well as be useful for the government to determine policy and regulatory directions to suppress virus transmission. Based on the Minister of Health Regulation on Medical Secrets which regulates the opening of medical records in a pandemic situation, there is a blurring of norms regarding legal certainty and procedures for opening medical records in a pandemic situation. To identify and analyze these problems, the researcher uses a normative legal research method with a conceptual approach and legislation. The results obtained that the opening of medical records of COVID-19 patients in a pandemic situation may only be opened to certain parties such as local government officials, hospital heads, and related parties who play a role in reducing the number of virus transmissions. In addition, the information in the medical record shown is only information related to epidemic control, so the patient's personal confidential information is maintained. KEYWORDS: Disclosure, Confidential, Medical Record, Patient, COVID-19